Development of Problem-Based Learning Model Physics Learning Tools to Improve Critical Thinking Skills of High School Students - Arini Hidayati; Munasir Munasir; Elok Sudibyo (IJORER : International Journal of Recent Educational Research, 2024)
Objective: Most EFL students need help to develop their speaking abilities. Due to their limited vocabulary, poor grammar, and lack of confidence, they could not practice speaking. Ten students from the English Department joined a study group to address these obstacles. Method: The procedure was carried out online. The teacher created a WhatsApp group as the initial class medium. He added to the vocabulary development and grammar education on the screen. The students studied the material on a video podcast to retell to meet the comprehension criteria, synchronizing their inputs with real life. They then describe a picture to hone their communication skills. They also transcript their story in order to make the spoken and written versions of it coincide. Results: After following the teacher's instructions to build sentences using the lexico-grammar technique, students can identify the grammatical conventions used in podcasts. They can adequately narrate pictures thanks to this type of learning. Their increased confidence fosters mature dialogue. The students' delivery will become more fluid due to the novelty of learning sentence construction through lexico-grammatical techniques and synchronizing it to podcast material. They acquired the ability to apply vocabulary and grammar norms contextually. It was evident from the way they described the images. To fit the needs of their students in the classroom, teachers might change them. It also encourages other researchers to continue their observations.